Gender‐related differences in patients undergoing transcatheter mitral valve interventions in clinical practice: 1‐year results from the German TRAMI registry. Issue 4 (24th June 2019) - Werner, Nicolas; Puls, Miriam; Baldus, Stephan; Lubos, Edith; Bekeredjian, Raffi; Sievert, Horst; Schofer, Joachim; Kuck, Karl‐Heinz; Möllmann, Helge; Hehrlein, Christoph; Nickenig, Georg; Boekstegers, Peter; et al.
Abstract: Objectives: Information on gender‐related differences in terms of baseline characteristics and clinical outcome of patients undergoing MitraClip® implantation in daily clinical practice have been studied in smaller populations previously. This study sought to additionally evaluate gender‐related differences in a larger German real‐world patient population. Methods and results: We analyzed data from the prospective and multicenter German TRAMI Registry. Between 08/2010 and 07/2013 327 women and 501 men underwent MitraClip® implantation for significant mitral valve regurgitation. Female patients were significantly older and showed higher rates of frailty compared to men. In contrast, men had significantly higher rates of comorbidities compared to women. The majority of patients underwent MitraClip® implantation for secondary mitral regurgitation, with no significant gender‐related differences. MitraClip® treatment was equally effective in terms of procedural results and residual mitral regurgitation in women and men and complication rates were low. However, in this real‐world analysis severe bleeding complications were significantly higher in women ( p = .02) and re‐intervention rates were significantly higher in men after MitraClip® treatment ( p = .02). Women showed less improvement in functional NYHA class after MitraClip® treatment compared to men at 1‐year follow‐up (FU; p  < .001). No significant differences between female and male patients were found in 1‐year mortality and in re‐hospitalization rates. Conclusion: In this analysis from a large prospective, multicenter real‐world registry MitraClip® implantation is safe and effective for treatment of significant mitral regurgitation with equal postprocedural results and mortality rates during 1‐year follow‐up. Men and women showed a persisting and significant clinical benefit at 1‐year FU after treatment. Complication and re‐intervention rates were low. Additional studies are needed to further evaluate our findings on increased bleeding complications and decreased functional improvement in women at 1‐year follow‐up after MitraClip® therapy.